FREE HEALTH GUARANTEE FOR THE POOR PEOPLE POST HEALTH LAW OMNIBUS LAW - Putra, I Putu Harry Suandana; Rato, Donimikus; Anggoro, Bayu Dwi (Awang Long Law Review, 2024)
The establishment of the National Social Security System is realized through Law Number 40 of 2004 concerning the National Social Security System (UU SJSN) which has a health insurance program, work accident insurance, old age insurance, pension insurance and death insurance. Health insurance as part of the social security system in Indonesia is indeed a form of social assistance program for health services for the poor and disadvantaged. This program is organized nationally to guarantee cross-subsidies in order to create comprehensive health services for the poor. The purpose of this study is to examine free health insurance for the poor after the health omnibus law related to the regulation that the central and regional governments are required to provide financial protection to the poor and disadvantaged through the health insurance program, so that they can access health services without cost barriers. The research method used is normative juridical. free health insurance for the poor after the health omnibus law in the future (establishing rights) is by creating a single institutional model in the form of an institution mandated by all people. This is important, because in this way the collection of funds will be realized quickly. A single institution in the sense of the organizer of the National Social Security System as a container or umbrella that covers program organizers, so that program implementation can be carried out by several program organizers, especially free health insurance for the poor. The single institution in question is led by a Director, under the National Social Security Council (DJSN), who is directly responsible to the President. The future model is the Free Health Insurance Agency for the Poor.